Appropriate electronic-learning technologies for mitigating the transmission of coronavirus disease pandemic 2019 in universities in north-central, nigeria - Arah, A. S; Audu, R; Adamu, D (Research Parks Publishing LLC, 2021)
The study identified the perception of educational technology lecturers on appropriate e-Learning technologies for mitigating the transmission of COVID-19 pandemic in Universities in North-Central, Nigeria. The research design used for this study was a descriptive survey research design, specifically, using cross-sectional study. The population of the study was all the 82 educational technology lecturers consisting of 55 males and 27 females from the nine Universities offering educational technology in North-Central, Nigeria. Total population sampling technique was used to select the whole population of the study. The instruments used for data collection was a structured questionnaire. Cronbach Alpha statistical method was used to determine the reliability indices of the instrument and found to be .89 and .90 respectively. The study employed the use of mean to answer the research questions and Analysis of Variance to test the null hypotheses. Findings from the study revealed among others that Zoom, Google Classroom, WhatsApp, YouTube, Telegram, EdX and Open edX, Udemy and LinkedIn Learning (Lynda) were appropriate e-Learning platforms for mitigating the transmission of COVID-19 pandemic in Universities in North-Central, Nigeria. The study recommended that, lecturers should adopt the used of the identified e-Learning platforms and contents delivery modes for mitigating the transmission of COVID-19 pandemic in Universities in North-Central, Nigeria.